Women’s Exploitation under Capitalism: A Marxist-Feminist Analysis of Rena Asyari’s Perempuan dan Mentalitas - Br. Saragih, Revi; Zuhriah, Lailatul; Purwarno, Purwarno (Pusat Studi Gender dan Anak - PSGA (Center for Gender and Child Studies) Institut Agama Islam Negeri Lhokseumawe, Aceh, 2025)
ABSTRACT ENGLISHThis research analyzes the exploitation of women in the short story Perempuan dan Mentalitas by Rena Asyari using a Marxist-Feminist approach. The background of this research departs from the phenomenon of exploitation of women in rural Indonesia who are trapped in the structure of capitalism and patriarchal culture, where women are used as cheap labour without equal access to education and self-development. This short story displays the reality of how young women are conditioned from the start to accept factory work as their only way of life, which reflects a form of systemic exploitation that is ideological and material in nature. This research uses a descriptive qualitative method with a close reading technique of literary texts. Marxist-Feminist theory is used to reveal the relationship between economic power, patriarchal culture, and false consciousness formed through consumption and normalization of domestic roles. The analysis shows four main forms of exploitation: the commodification of women's labour, patriarchal ideology and structural submission, consumerism as a distraction of consciousness, and women and the double burden. The short story illustrates how the capitalist system not only drains women physically, but also limits their consciousness and freedom through the internalization of social norms. The conclusion of this study confirms that literature can be an effective medium of social criticism to expose the structured exploitation of women. This study also emphasizes the importance of critical consciousness, access to education, and systemic change as absolute conditions towards women's liberation in a capitalist-patriarchal society. ABSTRACT INDONESIANPenelitian ini menganalisis eksploitasi perempuan dalam cerpen Perempuan dan Mentalitas karya Rena Asyari menggunakan pendekatan Marxis-Feminis. Latar belakang penelitian ini berangkat dari fenomena eksploitasi perempuan di pedesaan Indonesia yang terjebak dalam struktur kapitalisme dan budaya patriarki, di mana perempuan digunakan sebagai tenaga kerja murah tanpa akses yang setara terhadap pendidikan dan pengembangan diri. Cerpen ini menggambarkan realitas bagaimana perempuan muda sejak awal dikondisikan untuk menerima pekerjaan pabrik sebagai satu-satunya cara hidup mereka, yang mencerminkan bentuk eksploitasi sistemik yang bersifat ideologis dan material. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pembacaan mendalam teks sastra. Teori Marxist-Feminist digunakan untuk mengungkap hubungan antara kekuasaan ekonomi, budaya patriarki, dan kesadaran palsu yang terbentuk melalui konsumsi dan normalisasi peran domestik. Analisis menunjukkan empat bentuk eksploitasi utama: komodifikasi tenaga kerja perempuan, ideologi patriarki dan penyerahan struktural, konsumerisme sebagai pengalihan kesadaran, dan beban ganda perempuan. Cerpen ini menggambarkan bagaimana sistem kapitalis tidak hanya menguras tenaga perempuan secara fisik, tetapi juga membatasi kesadaran dan kebebasan mereka melalui internalisasi norma-norma sosial. Penelitian ini menegaskan bahwa sastra dapat menjadi medium kritik sosial yang efektif untuk mengungkap eksploitasi terstruktur terhadap perempuan. Penelitian ini juga menekankan pentingnya kesadaran kritis, akses terhadap pendidikan, dan perubahan sistemik sebagai syarat mutlak menuju pembebasan perempuan dalam masyarakat kapitalis-patriarkal.